A huggable device can reduce the stress of calling an unfamiliar person on the phone for individuals with ASD - Sumioka, Hidenobu (PLoS One, 2021)
Individuals with autism spectrum disorders (ASD) are often not comfortable during mobile-phone conversations with unfamiliar people. “Hugvie” is a pillow with a human-like shape that has been designed to provide users with the tactile sensation of hugging another person during phone conversations to promote feelings of comfort and trust in the speaker toward their conversation partners. Our primary aim was to examine whether physical contact by hugging a Hugvie could reduce the stress of speaking with an unfamiliar person on the phone in individuals with ASD. We enrolled 24 individuals and requested them to carry out phone conversations either using only a mobile phone or using a mobile phone along with the Hugvie. All participants in both groups completed questionnaires designed to evaluate their self-confidence while talking on the phone, and also provided salivary cortisol samples four times each day. Our analysis revealed that the medium of communication was a significant factor, indicating that individuals with ASD who spoke with an unfamiliar person on the phone while hugging a Hugvie had stronger self-confidence and lower stress levels than those who did not use Hugvie. Hence, we recommend that huggable devices be used as adjunctive tools to support individuals with ASD during telephonic conversations with unfamiliar people.